Viewing gallery inside Corporation Hall - Ghosh, Ayan (Jio Institute, 2023)
The viewing gallery inside the Corporation Hall. The hall was extensively damaged in a fire outbreak and was restored in 2000-01 by conservation architect Vikas Dilawari. Visitors need to climb up a cast-iron spiral staircase to reach the viewing gallery above, an idea Stevens borrowed from the Glasgow City Chambers, in Glasgow, Scotland.